Measurement and monitoring of safety: impact and challenges of putting a conceptual framework into practice - Chatburn, Eleanor (BMJ Qual Saf, 2018)
BACKGROUND: The Measurement and Monitoring of Safety Framework provides a conceptual model to guide organisations in assessing safety. The Health Foundation funded a large-scale programme to assess the value and impact of applying the Framework in regional and frontline care settings. We explored the experiences and reflections of key participants in the programme. METHODS: The study was conducted in the nine healthcare organisations in England and Scotland testing the Framework (three regional improvement bodies, six frontline settings). Post hoc interviews with clinical and managerial staff were analysed using template analysis. FINDINGS: Participants reported that the Framework promoted a substantial shift in their thinking about how safety is actively managed in their environment. It provided a common language, facilitated a more inquisitive approach and encouraged a more holistic view of the components of safety. These changes in conceptual understanding, however, did not always translate into broader changes in practice, with many sites only addressing some aspects of the Framework. One of the three regions did embrace the Framework in its entirety and achieved wider impact with a range of interventions. This region had committed leaders who took time to fully understand the concepts, who maintained a flexible approach to exploring the utility of the Framework and who worked with frontline staff to translate the concepts for local settings. CONCLUSIONS: The Measuring and Monitoring of Safety Framework has the potential to support a broader and richer approach to organisational safety. Such a conceptually based initiative requires both committed leaders who themselves understand the concepts and more time to establish understanding and aims than might be needed in a standard improvement programme.